MODERN METHODS OF FORMING COMPETENCE IN SCHOOL STUDENTS IN WORKING WITH INFORMATION - Usmonaliyeva Risolat Umaraliyevna (American Journals Publishing, 2024)
This article is devoted to modern methods of forming schoolchildren's competence in working with information, and analyzes the effectiveness of using innovative and interactive methods for working with information.
Keywords: Students, competence work, social life, the problems of everyday life, to find information.